Pieter Bruegel the Elder and religion - Kaschek, Bertram; Müller, Jürgen; Buskirk, Jessica (Brill's studies in intellectual history, 2018)
Pieter Bruegel the Elder and religion: a historiographical introduction / Bertram Kaschek -- Of Birdnesters and Godsearchers: a new interpretation of Pieter Bruegel the Elder's The Beekeepers / Jürgen Müller -- Peter Bruegel and the problem of vision / Larry Silver -- Virtue or tyranny? Pieter Bruegel, Justitia, and the myth of the Inquisition / Gerd Schwerhoff -- The First Temptation of Christ: an evolving iconographic trope in sixteenth-century Antwerp / Jessica Buskirk -- The imaginarium of death: Pieter Bruegel's The Triumph of Death / Anna Pawlak -- Evidentiae resurrectionis: on the mystery discerned but not seen in Pieter Bruegel's Resurrection of ca. 1562-1563 / Walter S. Melion -- Falling idols, rising icons: Bruegel's Flight Into Egypt and the embeddedness of sacred images in nature / Ralph Dekoninck -- Pieter Bruegel's Hunters in the Snow and Insidiosus Auceps as trap images / Michel Weemans